Smile - Telgemeier, Raina (New York : Graphix, an imprint of Scholastic, 2010)
The author relates, in graphic form, her experiences after she injured her two front teeth and had to have surgeries and wear embarrassing braces and headgear, all while also dealing with the trials and tribulations of middle school.
Book Links (A.L.A.)
Notable/Best Books (A.L.A.)
School Library Journal
Book Links (A.L.A.), October 2010
Booklist, December 2009
Bulletin (Center for Children's books), March 2010
Keywords: Telgemeier, Raina -- Comic books, strips, etc. -- Juvenile literature; Telgemeier, Raina -- Cartoons and comics; Telgemeier, Raina -- Comic books, strips, etc; Beauty, Personal -- Comic books, strips, etc -- Juvenile literature; Self-esteem in adolescence -- Comic books, strips, etc -- Juvenile literature; Teenage girls -- Comic books, strips, etc -- Juvenile literature; Youth -- Dental care -- Comic books, strips, etc -- Juvenile literature; Beauty, Personal -- Cartoons and comics; Cartoons and comics; Self-esteem -- Cartoons and comics; Teenage girls -- Cartoons and comics; Youth -- Dental care -- Cartoons and comics; Comic books, strips, etc; Girls -- Comic books, strips, etc; Personal appearance -- Comic books, strips, etc; Self-esteem -- Comic books, strips, etc; Teenagers -- Comic books, strips, etc; Youth -- Dental care -- Comic books, strips, etc